Mempererat Regional Asean Melalui Tatanan Hukum Keantariksaan: Peluang Dan Tantangan Bagi Indonesia - Nugraha, Ridha Aditya; Paramita, Kartika (Jurnal Hukum & Pembangunan, 2019)
The outer space has become a forum for international cooperation. History has revealed that many countries with different ideologies could work together when it comes to space activities. The existence of the Association of South East Asian Nations (ASEAN) as a subject of international law with ten member states shall test that premise. The actualization of regional cooperation on space activities could be in many forms, one of them is through the establishment of an ASEAN Space Agency. In a smaller scale, considering there is no legal system applied in the ASEAN level, arranging a joint satellite operation seems rather realistic. Both scenarios could become solutions to answer several actual issues, such as utilizing Geostationary Orbit (GSO) slots for Indonesia as well as determining space activity goals in the ASEAN region.